Direct Graphene Transfer and Its Application to Transfer Printing Using Mechanically Controlled, Large Area Graphene/Copper Freestanding Layer. (25th April 2018) - Seo, Jeongmin; Kim, Cheogyu; Ma, Boo Soo; Lee, Tae‐Ik; Bong, Jae Hoon; Oh, Joong Gun; Cho, Byung Jin; Kim, Taek‐Soo
Abstract: Direct graphene transfer is an attractive candidate to prevent graphene damage, which is a critical problem of the conventional wet transfer method. Direct graphene transfer can fabricate the transferred graphene film with fewer defects by using a polymeric carrier. Here a unique direct transfer method is proposed using a 300 nm thick copper carrier as a suspended film and a transfer printing process by using the polydimethylsiloxane (PDMS) stamp under controlled peeling rate and modulus. Single and multilayer graphene are transferred to flat and curved PDMS target substrate directly. With the transfer printing process, the transfer yield of a trilayer graphene with 1000 µm s −1 peeling rate is 68.6% of that with 1 µm s −1 peeling rate. It is revealed that the graphene transfer yield is highly related to the storage modulus of the PDMS stamp: graphene transfer yield decreases when the storage modulus of the PDMS stamp is lower than a specific threshold value. The relationship between the graphene transfer yield and the interfacial shear strain of the PDMS stamp is studied by finite‐element method simulation and digital image correlation. Abstract : A direct graphene transfer method using a 300 nm thick copper carrier as a suspended film and its transfer printing process are demonstrated. The graphene transfer yield is related to the peeling rate and the storage modulus of the polydimethylsiloxane (PDMS) stamp. Graphene transfer yield decreases when the storage modulus of the PDMS stamp is lower than a specific threshold value.